Moderating Effects of Social Norms and Alcohol Consumption on Message Framing in Responsible Drinking Campaigns: Value from Deviance Regulation Theory. Issue 7 (6th June 2020) - Park, Sun-Young; Son, Hyunsang; Lee, Jaejin; Go, Eun
ABSTRACT: This study examined how the interplay between message framing and social norms affected college students' responses to advertisements and their intentions to drink responsibly, using the lens of deviance regulation theory. The results showed more favorable responses to gain-framed messaging than loss-framed messaging, especially among college students who believed that most of their peers use alcohol irresponsibly (i.e., they observed an unhealthy social norm). This study also investigated how the moderating effects of social norms on message framing differ depending on the level of individual alcohol consumption, and found that the deviance regulation effects on intention to drink responsibly were mitigated among heavy drinkers. The findings suggest strategic potential for using messaging, social context, and individual factors to develop effective campaigns that promote responsible drinking.